(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article explores the morphological and functional factors leading to comitant strabismus and outlines measures for its prevention and conservative treatment. It highlights the establishment of specialized kindergartens in the former Soviet Union and Uzbekistan, focusing on their success in treating children with vision impairments. These kindergartens, pioneered by scientists like Professor T.P. Kashchenko and Associate Professor A.Kh. Sharapova, combined therapeutic exercises, advanced ophthalmologic tools, and innovative methodologies to restore binocular vision and improve visual health in children. The article also emphasizes the importance of early diagnosis and intervention for visual disorders like amblyopia, myopia, and strabismus, presenting these facilities as effective solutions for fostering children’s overall development.